2012
DOI: 10.1111/j.1442-2018.2012.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intimate partner violence on postpartum women's health in northeastern Thailand

Abstract: In the present study, we investigated the prevalence of psychological, physical, and sexual violence perpetrated by an intimate partner, and the effects on health status of postpartum women who gave birth at two tertiary hospitals in northeastern Thailand. Participants were recruited during pregnancy and interviewed at 6 weeks' postpartum. Measures included the Short Form 12-Item Health Survey, Psychological Maltreatment of Women Inventory, and Severity of Violence against Women scale. Participants reported hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
12
2
Order By: Relevance
“…This prevalence seems to be comparable with similar studies in similar settings (2.2% physical abuse in six European countries) [ 4 ] and Asian countries (ranging from 1.2% in Japan to 4.0% in Thailand) [ 5 ]. In some local surveys in Thailand the prevalence of past 12 month intimate partner violence ranged from 4.8 to 26.6% [ 6 8 ]. One possible explanation for the higher prevalence in the latter surveys is that detailed validated intimate partner violence scales were used, while our intimate partner violence prevalence was obtained on the basis of two screening questions that did not include the range of women’s experiences of intimate partner violence [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This prevalence seems to be comparable with similar studies in similar settings (2.2% physical abuse in six European countries) [ 4 ] and Asian countries (ranging from 1.2% in Japan to 4.0% in Thailand) [ 5 ]. In some local surveys in Thailand the prevalence of past 12 month intimate partner violence ranged from 4.8 to 26.6% [ 6 8 ]. One possible explanation for the higher prevalence in the latter surveys is that detailed validated intimate partner violence scales were used, while our intimate partner violence prevalence was obtained on the basis of two screening questions that did not include the range of women’s experiences of intimate partner violence [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Past year intimate partner violence during pregnancy was 2.0% in Cambodia, 0.4% in the Philippines, 1.2% in Japan and 3.8% in rural and 4.2% in urban Thailand [ 5 ]. Other local surveys in Thailand found among pregnant women that 4.8% had experienced physical intimate partner violence during pregnancy and 4.8% sexual violence in the past 12 months [ 6 ], and in another study Saito et al [ 7 ] found among prenatal women that 26.6% were exposed to overall threats and acts of physical violence during their current pregnancy, and Saito et al [ 8 ] found among post-partum women that overall 9.5% were exposed to threats and physical violence and 11.3% sexual violence. There is a lack of studies on the prevalence and correlates of sexual assault in the context of intimate partner violence in Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Social HS was impaired in abused postpartum women compared to non-abused postpartum women in one study [67]. However, another study found that social HS was only impaired in postpartum women experiencing both psychological and physical abuse compared to non-abused postpartum women [68].…”
Section: Social Health Statusmentioning
confidence: 95%
“…One study found worse mental HS in abused postpartum women compared to non-abused postpartum women [67]. The abuse consisted of physical, psychological, or sexual abuse, but could also consist of a combination of abuses.…”
Section: Mental Health Statusmentioning
confidence: 98%
“…A recent meta-analysis established the prevalence of IPV during pregnancy to be anywhere from 4.8 to 63.4% [32], depending on the definition, assessment tools and population. The postpartum period is also considered a time of increased risk of IPV for new mothers [35, 36], with prevalence rates ranging from 2–25% [37]. During pregnancy, IPV may increase in more frequently [38] and more severely [39].…”
Section: Introductionmentioning
confidence: 99%